Agreement between Older Persons and their Surrogate Decision Makers Regarding Participation in Advance Care Planning - Fried, Terri R. (2011)
OBJECTIVES: To examine agreement between older persons and their surrogates regarding participation in advance care planning (ACP). DESIGN: Observational cohort study. SETTING: Community PARTICIPANTS: Persons age ≥ 65 and the individual they identified as most likely to make treatment decisions on their behalf. MEASUREMENTS: Older persons were asked about participation in four activities: 1. Completion of living will; 2. Completion of health care proxy; 3. Communication regarding views about life-sustaining treatment; 4. Communication regarding views about quality versus quantity of life. Surrogates were asked whether they believed the older person had completed these activities. RESULTS: Of 216 pairs, 81% agreed about whether a living will had been completed [k = .61, 95% confidence interval (CI) .51, .72]. Only 68% of pairs agreed about whether a health care proxy had been completed (k = .39, 95% CI .29, .50), 64% agreed about whether they had communicated regarding life-sustaining treatment (k = .22, 95% CI .09, .35), and 62% agreed about whether they had communicated regarding quality versus quantity of life (k = .23, 95% CI .11, .35). CONCLUSIONS: While agreement between older persons and their surrogates regarding living will completion was good, agreement about participation in other aspects of ACP was fair to poor. Additional study is necessary to determine who is providing the most accurate report of objective ACP components and whether agreement regarding participation in ACP is associated with greater shared understanding of patients’ preferences.